Dysregulation of neutrophil death in sepsis - Zhu, Cheng-long; Wang, Yi; Liu, Qiang; Li, Hui-ru; Yu, Chang-meng; Li, Peng; Deng, Xiao-ming; Wang, Jia-feng (Frontiers in Immunology, 2022)
Sepsis is a prevalent disease that has alarmingly high mortality rates and, for several survivors, long-term morbidity. The modern definition of sepsis is an aberrant host response to infection followed by a life-threatening organ dysfunction. Sepsis has a complicated pathophysiology and involves multiple immune and non-immune mediators. It is now believed that in the initial stages of sepsis, excessive immune system activation and cascading inflammation are usually accompanied by immunosuppression. During the pathophysiology of severe sepsis, neutrophils are crucial. Recent researches have demonstrated a clear link between the process of neutrophil cell death and the emergence of organ dysfunction in sepsis. During sepsis, spontaneous apoptosis of neutrophils is inhibited and neutrophils may undergo some other types of cell death. In this review, we describe various types of neutrophil cell death, including necrosis, apoptosis, necroptosis, pyroptosis, NETosis, and autophagy, to reveal their known effects in the development and progression of sepsis. However, the exact role and mechanisms of neutrophil cell death in sepsis have not been fully elucidated, and this remains a major challenge for future neutrophil research. We hope that this review will provide hints for researches regarding neutrophil cell death in sepsis and provide insights for clinical practitioners.